Accessory Genome Dynamics of Local and Global Staphylococcus pseudintermedius Populations - Bruce, Spencer A.; Smith, Joshua T.; Mydosh, Jennifer L.; Ball, John; Needle, David B.; Gibson, Robert; Andam, Cheryl P. (Frontiers in Microbiology, 2022)
Staphylococcus pseudintermedius is a major bacterial colonizer and opportunistic pathogen in dogs. Methicillin-resistant S. pseudintermedius (MRSP) continues to emerge as a significant challenge to maintaining canine health. We sought to determine the phylogenetic relationships of S. pseudintermedius across five states in the New England region of the United States and place them in a global context. The New England dataset consisted of 125 previously published S. pseudintermedius genomes supplemented with 45 newly sequenced isolates. The core genome phylogenetic tree revealed many deep branching lineages consisting of 142 multi-locus sequence types (STs). In silico detection of the mecA gene revealed 40 MRSP and 130 methicillin-susceptible S. pseudintermedius (MSSP) isolates. MRSP were derived from five structural types of SCCmec, the mobile genetic element that carries the mecA gene conferring methicillin resistance. Although many genomes were MSSP, they nevertheless harbored genes conferring resistance to many other antibiotic classes, including aminoglycosides, macrolides, tetracyclines and penams. We compared the New England genomes to 297 previously published genomes sampled from five other states in the United States and 13 other countries. Despite the prevalence of the clonally expanding ST71 found worldwide and in other parts of the United States, we did not detect it in New England. We next sought to interrogate the combined New England and global datasets for the presence of coincident gene pairs linked to antibiotic resistance. Analysis revealed a large co-circulating accessory gene cluster, which included mecA as well as eight other resistance genes (AAC(6')-Ie-APH(2")-Ia, aad(6), APH(3')-IIIa, SAT-4, ermB CAT, blaZ, and tetM). Furthermore, MRSP isolates carried significantly more accessory genes than their MSSP counterparts. Our results provide important insights to the evolution and geographic spread of high-risk clones that can threaten the health of our canine companions.